The development and status of Bt rice in China. Issue 3 (15th September 2015) - Li, Yunhe; Hallerman, Eric M.; Liu, Qingsong; Wu, Kongming; Peng, Yufa
Summary: Multiple lines of transgenic rice expressing insecticidal genes from the bacterium Bacillus thuringiensis ( Bt ) have been developed in China, posing the prospect of increases in production with decreased application of pesticides. We explore the issues facing adoption of Bt rice for commercial production in China. A body of safety assessment work on Bt rice has shown that Bt rice poses a negligible risk to the environment and that Bt rice products are as safe as non‐ Bt control rice products as food. China has a relatively well‐developed regulatory system for risk assessment and management of genetically modified (GM) plants; however, decision‐making regarding approval of commercial production has become politicized, and two Bt rice lines that otherwise were ready have not been allowed to enter the Chinese agricultural system. We predict that Chinese farmers would value the prospect of increased yield with decreased use of pesticide and would readily adopt production of Bt rice. That Bt rice lines may not be commercialized in the near future we attribute to social pressures, largely due to the low level of understanding and acceptance of GM crops by Chinese consumers. Hence, enhancing communication of GM crop science‐related issues to the public is an important, unmet need. While the dynamics of each issue are particular to China, they typify those in many countries where adoption of GM crops has been not been rapid; hence, the assessment of these dynamics might inform resolution of these issues in other countries.